Pemanfaatan Media Interaktif Untuk Meningkatkan Minat Belajar Siswa Pada Pembelajaran PAI Di SDN 004 Cenaku Kecil - Aulia Putri; Dika Merlianda; Nur Azizah (4, 2026)
This study is motivated by the low level of students’ interest in learning Islamic Religious Education (PAI), which is still dominated by conventional teaching methods. Theoretically, effective learning should be able to increase student engagement and motivation through innovative media. Therefore, this study aims to analyze the use of interactive media in improving students’ learning interest in PAI at SDN 004 Cenaku Kecil. This study employs a descriptive qualitative approach. The research subjects consist of PAI teachers as the main informants, as well as the principal and students as supporting informants. Data collection techniques include observation, interviews, and documentation. The data are analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with data validity ensured through source and method triangulation. The results show that students’ learning interest before the use of interactive media was low due to monotonous teaching. The use of interactive media is able to improve students’ interest, participation, and understanding. The media used include instructional videos, digital presentations, images, and educational applications. Supporting factors include school facilities, institutional support, and students’ enthusiasm, while the obstacles include limited internet access, time constraints, and teachers’ technological skills. This study concludes that interactive media play an important role in creating more effective learning. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya minat belajar siswa pada pembelajaran Pendidikan Agama Islam (PAI) yang masih didominasi metode konvensional. Secara teoritis, pembelajaran efektif harus mampu meningkatkan keterlibatan dan motivasi siswa melalui inovasi media. Oleh karena itu, penelitian ini bertujuan menganalisis pemanfaatan media interaktif dalam meningkatkan minat belajar siswa pada pembelajaran PAI di SDN 004 Cenaku Kecil. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Subjek penelitian terdiri dari guru PAI sebagai informan utama serta kepala sekolah dan siswa sebagai informan pendukung. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Data dianalisis menggunakan model interaktif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan, dengan uji keabsahan melalui triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa minat belajar siswa sebelum penggunaan media interaktif masih rendah karena pembelajaran monoton. Penggunaan media interaktif mampu meningkatkan minat, keaktifan, dan pemahaman siswa. Media yang digunakan meliputi video pembelajaran, presentasi digital, gambar, dan aplikasi edukatif. Faktor pendukung berupa fasilitas sekolah, dukungan pihak sekolah, dan antusiasme siswa, sedangkan hambatan meliputi keterbatasan jaringan, waktu, dan kemampuan guru. Penelitian ini menyimpulkan bahwa media interaktif berperan penting dalam menciptakan pembelajaran yang lebih efektif.